Associations of maternal circulating 25‐hydroxyvitamin D3 concentration with pregnancy and birth outcomes. (11th September 2014) - Rodriguez, A; García‐Esteban, R; Basterretxea, M; Lertxundi, A; Rodríguez‐Bernal, C; Iñiguez, C; Rodriguez‐Dehli, C; Tardón, A; Espada, M; Sunyer, J; Morales, E
<x xml:space="preserve">Abstract</x> Objective To investigate the association of maternal circulating 25‐hydroxyvitamin D3 [25(OH)D3] concentration with pregnancy and birth outcomes. Design Prospective cohort study. Setting Four geographical areas of Spain, 2003–2008. Population Of 2382 mother–child pairs participating in the INfancia y Medio Ambiente (INMA) Project. Methods Maternal circulating 25(OH)D3 concentration was measured in pregnancy (mean [SD] 13.5 [2.2] weeks of gestation). We tested associations of maternal 25(OH)D3 concentration with pregnancy and birth outcomes. Main outcome measures Gestational diabetes mellitus (GDM), preterm delivery, caesarean section, fetal growth restriction (FGR) and small‐for‐gestational age (SGA), anthropometric birth outcomes including weight, length and head circumference (HC). Results Overall, 31.8% and 19.7% of women had vitamin D insufficiency [25(OH)D3 20–29.99 ng/ml] and deficiency [25(OH)D3 < 20 ng/ml], respectively. After adjustment, there was no association between maternal 25(OH)D3 concentration and risk of GDM or preterm delivery. Women with sufficient vitamin D [25(OH)D3 ≥ 30 ng/ml] had a decreased risk of caesarean section by obstructed labour compared with women with vitamin D deficiency [relative risk (RR) = 0.60, 95% CI 0.37, 0.97). Offspring of mothers with higher circulating 25(OH)D3 concentration tended to have smaller HC [coefficient (SE) per doubling concentration of 25(OH)D3, −0.10 (0.05), P = 0.038]. No significant associations were found for other birth outcomes. Conclusion This study did not find any evidence of an association between vitamin D status in pregnancy and GDM, preterm delivery, FGR, SGA and anthropometric birth outcomes. Results suggest that sufficient circulating vitamin D concentration [25(OH)D3 ≥ 30 ng/ml] in pregnancy may reduce the risk of caesarean section by obstructed labour.